2002
DOI: 10.1136/jcp.55.5.359
|View full text |Cite
|
Sign up to set email alerts
|

Multiparameter flow cytometry as a tool for the detection of micrometastatic tumour cells in the sentinel lymph node procedure of patients with breast cancer

Abstract: Aim: To investigate whether multiparameter flow cytometry (MP-FCM) can be used for the detection of micrometastasis in sentinel lymph nodes (SLNs) in breast cancer. Methods: Formalin fixed, paraffin wax embedded sentinel lymph nodes (n = 238) from 98 patients were analysed. For each lymph node, sections for haematoxylin and eosin (H&E) staining and immunohistochemistry (IHC) for cytokeratin (MNF116) were cut at three levels with a distance of 500 µm. The intervening material was used for MP-FCM. Cells were imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 30 publications
(29 reference statements)
2
26
0
Order By: Relevance
“…However, the rate of LRP-positive cells evaluated by flow cytometry is higher than that previously reported for LRP expression evaluated by immunohistochemistry (Dingemans et al 1996;Volm et al 1997;Harada et al 2003;Raybarova et al 2004). This difference can probably be explained by a higher sensitivity of flow cytometry analysis compared with immunohistochemistry (Leers et al 2002). Similarly, LRP was detected in bronchial epithelial cells in our study as in other studies (Nooter et al 1995), suggesting a role of LRP in the cell detoxification process for cells localized at the air-tissue interface (Dingemans et al 1996;Izquierdo et al 1996a) where detoxification mechanisms are particularly well developed.…”
Section: Discussionsupporting
confidence: 42%
“…However, the rate of LRP-positive cells evaluated by flow cytometry is higher than that previously reported for LRP expression evaluated by immunohistochemistry (Dingemans et al 1996;Volm et al 1997;Harada et al 2003;Raybarova et al 2004). This difference can probably be explained by a higher sensitivity of flow cytometry analysis compared with immunohistochemistry (Leers et al 2002). Similarly, LRP was detected in bronchial epithelial cells in our study as in other studies (Nooter et al 1995), suggesting a role of LRP in the cell detoxification process for cells localized at the air-tissue interface (Dingemans et al 1996;Izquierdo et al 1996a) where detoxification mechanisms are particularly well developed.…”
Section: Discussionsupporting
confidence: 42%
“…6,23 This difference can probably be explained by a higher sensitivity of flow cytometry analysis compared to immunohistochemistry. 24 This biparametric analysis demonstrated that the MRP ratio, i.e., the MRP1 expression at the individual cell level, was significantly higher in DNA aneuploid cells than in DNA diploid cells. These results were confirmed by analysis of a selected group of tumors containing more than 80% of carcinomatous cells.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of the aforementioned PCR based methods can significantly increase the apparent 'false-negative' rate of conventional analysis [22]. Multi-parameter flow cytometry, applied to permanently fixed sections, has also been shown to detect MM within SLNs [23]. Adjuncts to the conventional human assessment of specimens have been shown to be effective.…”
Section: Analysis Of the Sentinel Lymph Nodementioning
confidence: 99%